2022
DOI: 10.3390/geriatrics7020030
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Subjective Cognitive Complaints and Executive Functions in Middle-Aged Adults as a Preclinical Stage of Dementia: A Systematic Review

Abstract: Subjective cognitive complaints correspond to a heterogeneous construct that frequently occurs in the early stages of older adult life. Despite being a common source of worry for middle-aged people, it can be underestimated when clinical and neuropsychological assessments discard any underlying pathological processes. Negative age stereotyping but also self-stereotyping can contribute to doing so. Although its diagnosis is a challenge, its implication as a possible predictor of mild cognitive impairment or dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
0
5
0
1
Order By: Relevance
“…This may indeed be responsible itself for the cognitive deficits that SCD individuals subjectively experience. Executive dysfunctions have been previously described in SCD populations [32][33][34]. Impairment of higher executive abilities, such as the divided attention or flexibility, may impact on free recall during memory tasks [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…This may indeed be responsible itself for the cognitive deficits that SCD individuals subjectively experience. Executive dysfunctions have been previously described in SCD populations [32][33][34]. Impairment of higher executive abilities, such as the divided attention or flexibility, may impact on free recall during memory tasks [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dysexecutive functioning has been reported along the continuum of pathological aging, including MCI and AD [ 34 , 56 ]. The impairment or decline of executive functions has also been reported in SCD, and it is considered an early sign of cognitive decline in pathological aging [ 30 , 34 , 35 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired executive function is considered an early sign of cognitive decline in the course of pathological aging [ 34 ]. In a recent systematic review, Webster-Cordero and Giménez-Llort found a relationship between cognitive complaints and early impairment of executive functions (i.e., working memory, initiative, cognitive flexibility, inhibition, planning) associated with AD cerebrospinal fluid biomarkers and reduced cortical volume in bilateral hippocampi and left frontal regions [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, neuroimaging techniques such as magnetoencephalography (MEG) reflect both learning/memory and executive functions and could be an independent biomarker of cognitive impairment [ 11 ]. This is important because psychiatric comorbidity is often a neglected confounding factor in studies of subjective cognitive complaints [ 12 ].…”
Section: Therapeutic Approaches To Restore Cognitive and Motor Tasks ...mentioning
confidence: 99%